ANALISIS TINGKAT KESEHATAN BANK PADA PT BANK MUAMALAT INDONESIA, Tbk DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING & CAPITAL) PERIODE 2013 - 2017 - Zakaria Hamzah, Zeze; Anggraini, Dewi (Economicus, 2019)
This study aims to determine the health level of Bank Muamalat in 2013-2017 in terms of aspects of Risk Profile, Good Corporate Governance, Earning & Capital. The data analysis technique used is the analysis of the soundness of the bank. The results of the study showed that during 2013-2017: (1) the Aspects of Risk Profile in NPF in 2013 were in the very healthy predicate, in 2014-2015 in the predicate of being quite healthy, in 2016-2017 in the predicate of health. FDR in 2013, 2014, 2015, 2016 and 2017 respectively in the title is quite healthy, healthy, quite healthy, quite healthy and healthy. (2) GCG aspects during 2013-2017 ranked 1 in very good condition, ranked 3 quite well, ranked 3 quite well, ranked 2 good and ranked 3 quite well. (3) Earning aspects of the 2013 ROA indicator are healthy, 2014-2017 are in a less healthy condition. ROE in 2013 was in a fairly healthy condition, 2014-2017 was in an unhealthy condition and BOPO in 2013 was quite healthy, 2014-2017 was in an unhealthy condition (4) Capital aspect with CAR value in 2013-2017 was in a very bad condition healthy. (5) The overall aspect of RGEC is in a less healthy condition with a composite rating of 4.